Determinan Preferensi Mantan Anggota Lembaga Keuangan Pailit dalam Akses Layanan BMT di Kecamatan Sekampung - Nurul Amalia Dewi (Journal Tafkirul Iqtishodiyyah, 2025)
This study aims to analyze the preferences of former members of a bankrupt microfinance institution regarding their interest in re-engaging in transactions with Baitul Maal wat Tamwil (BMT) in Sekampung District. This research employs a qualitative approach, with primary data obtained through in-depth interviews with former members of BMT Al-Hasanah that experienced bankruptcy. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing and verification. The findings reveal two distinct preference groups. The first group still shows interest in conducting transactions with BMT, driven by strong social relations, positive prior experiences, and a favorable perception of the institution’s reputation. The second group no longer has interest in re-engaging with BMT, which is influenced by negative past experiences, community concerns and disappointment toward BMT, unsatisfactory service quality, poor financial management, weak oversight, and psychological trauma caused by the bankruptcy incident. These findings indicate that the preferences of former members are shaped not only by economic considerations but also by psychological factors and the social relationships built throughout their experience.